Climate (In)justice: An Intersectional Feminist Analysis of Disaster Management in Antigua and Barbuda in the Aftermath of Hurricane Irma - Kotsinas, Melina (Politikon: The IAPSS Journal of Political Science, 2020)
This article discusses disaster management in the aftermath of Hurricane Irma in Antigua and Barbuda. Vulnerability and resilience of individuals and groups in relation to disaster management are placed within structures such as gender, sexuality, (dis)ability, age and socio-economic status, etc. How stakeholders within disaster management such as the Directorate of Gender Affairs, the National Office of Disaster Services, and District Coordinators, understand and respond to vulnerability and resilience might reinforce or challenge such structures and power relations. This study draws on insights from intersectional feminism to examine which social categories are made (in)visible, and how power relations are reproduced or challenged. It shows that some social categories (age, family status, class and occupation) in relation to gender gain more attention than others (disability and sexuality). The understandings and responses make some social categories that have previously been invisible visible, and heteronormative and patriarchal processes were both reproduced and challenged.